2022
DOI: 10.1002/agj2.21181
|View full text |Cite
|
Sign up to set email alerts
|

Interactive soybean variable‐rate seeding simulator for farmers

Abstract: Seed expense is a critical component affecting soybean (Glycine max L.) production cost. Achieving potential benefits of adjusting seeding rates by yield environment requires translation from theory to practice through decision support tools. This article introduces the soybean variable-rate seeding (VRS) simulator, an interactive web-tool designed to facilitate VRS decisions. A group of agronomists and farmers provided input and feedback to the tool's original design, usability, interactive features, and tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The estimated per‐hectare profit gain from applying VRS compared to URS (i.e., π0.28em0.28emπU${\pi ^*}\; - \;{\pi _U}$) ranges from $0.20 to $30.60 ha −1 . The estimated profit gain is comparable in magnitude to Correndo et al.’s (2022) estimation—$5–57 ha −1 . The site‐years OH‐C1‐2017 and MI‐W1‐2018 have the highest profit gains, both near $30 ha −1 .…”
Section: Resultssupporting
confidence: 76%
“…The estimated per‐hectare profit gain from applying VRS compared to URS (i.e., π0.28em0.28emπU${\pi ^*}\; - \;{\pi _U}$) ranges from $0.20 to $30.60 ha −1 . The estimated profit gain is comparable in magnitude to Correndo et al.’s (2022) estimation—$5–57 ha −1 . The site‐years OH‐C1‐2017 and MI‐W1‐2018 have the highest profit gains, both near $30 ha −1 .…”
Section: Resultssupporting
confidence: 76%
“…VRS in corn production, compared to uniform rate seeding (URS), resulted in a potential economic benefit ranging from $0.15 to $12.83 per hectare, depending on the availability of information and technology adoption (Bullock et al, 1998). In addition, implementing variable rate seeding using the soybean VRS simulator resulted in potential profit improvements ranging from $5 to $57 per hectare compared to typical fixed seeding rate choices (Correndo et al, 2022). This demonstrates the potential economic benefits of adopting VRS in different crop production systems.…”
Section: Variable Rate Seeding(vrs)mentioning
confidence: 99%
“…Focusing on these last points, Neufeldt et al (2013) suggested that a systematic gathering and integration of data, overcoming spatial and temporal dimensions differences, is needed to plan agricultural interventions to support the food security agenda. More recently, and from the agriculture side, a few digital tools were generated in a relevant effort to demonstrate a potential path forward on moving from research outcomes to actionable decisions (e.g., Laurent et al, 2021;Correndo et al, 2022). Therefore, as demonstrated by recent agricultural developments, using digital tools reduces the effort and time needed to overcome the challenges to planning agricultural interventions (McCampbell et al, 2021) and potentially increases adoption.…”
Section: Introductionmentioning
confidence: 99%